2015
DOI: 10.1007/s12665-015-4416-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the variability in Escherichia coli (E. coli) throughout storm events at a karst spring in northwestern Arkansas, United States

Abstract: In northwestern Arkansas, karst aquifers have experienced degraded water quality due to impacts of landuse changes, such as increased urbanization or intensification of agriculture. Water quality at a karst spring was characterized by quantifying the variability of fecal-indicator bacteria, specifically Escherichia coli (E. coli), throughout base-flow periods and storm events. Waterquality change over time was assessed using an intermittent record of nitrate and chloride data since the 1990s. A Geographic Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Travel time for impaired runoff from upstream areas to the creek ranges from 30 min to 2 h, indicating the timing of the first flush. This agrees with Mallin et al (2001), who found fecal coliform had a strong correlation with precipitation within 24 h. The faster E. coli-precipitation response at the spring is likely related to the region's karst topography and was similarly observed at a spring in Arkansas (Knierim et al, 2015). Epikarst systems occur in carbonate rocks that are extensively weathered near the surface; they represent an area of the vadose zone in which groundwater or contaminants may be stored in a perched aquifer before infiltrating the carbonate rocks below (Klimchouk, 2004).…”
Section: Comparison Of Sampling Sitessupporting
confidence: 89%
“…Travel time for impaired runoff from upstream areas to the creek ranges from 30 min to 2 h, indicating the timing of the first flush. This agrees with Mallin et al (2001), who found fecal coliform had a strong correlation with precipitation within 24 h. The faster E. coli-precipitation response at the spring is likely related to the region's karst topography and was similarly observed at a spring in Arkansas (Knierim et al, 2015). Epikarst systems occur in carbonate rocks that are extensively weathered near the surface; they represent an area of the vadose zone in which groundwater or contaminants may be stored in a perched aquifer before infiltrating the carbonate rocks below (Klimchouk, 2004).…”
Section: Comparison Of Sampling Sitessupporting
confidence: 89%
“…The presence of fecal contamination within Blowing Springs Cave was shown to be correlated to the increase of discharge within the cave, confirming the study by Knierim et al (2015). The source of the fecal contamination is unknown, though it is hypothesized to originate from septic tanks within the recharge area.…”
Section: Resultssupporting
confidence: 75%
“…C and k are constants of 0.5779 and 0.002903 (USBR, 2007). Discharge for BSC was also estimated using data from a USGS station on Little Sugar creek (USGS 07188838) and the established relationship by Knierim et al (2015).…”
Section: Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…The control of these porosity types on permeability leads to two end-member flow types-diffuse flow (Alley and others, 2002;Ghasemizadeh and others, 2012), in which slower time-averaged flow through diffuse flow paths allows for sustained groundwater input to streams and springs and focused flow, which provides extremely rapid response and transit times during precipitation events. The Ozark system is susceptible to surface-derived contamination because focused flow paths-including karst features such as sinkholes, losing-stream segments, and dissolution-enlarged fractures-rapidly transmit surface water to groundwater aquifers (Adamski and others, 1997;Peterson and others, 2000;Knierim, Hays, and Bowman, 2015). Groundwater flow is ultimately controlled by lithologies exposed at the surface that receive recharge, stratigraphic relations among hydrogeologic units, geologic structure, and modification of carbonate bedrock during distinct periods of karstification over time (Kresse and others, 2014).…”
Section: Hydrogeologic Frameworkmentioning
confidence: 99%